PENERAPAN GOOD CORPORATE GOVERNANCE (GCG) MELALUI REFORMASI BIROKRASI PADA DIREKTORAT NAVIGASI PENERBANGAN - Aziqri Muharam; Dejehave Al Jannah (Jurnal Ilmiah Global Education, 2023)
There are many problems in governance, it is felt that the services provided to the community still have many things that need to be improved. Excellent, easy, accountable and transparent public services need to be implemented followed by policies as a way out. The purpose of this research is to be able to find problem points or advantages of implementing Good Corporate Governance (GCG) and to be able to provide recommendations regarding the progress of bureaucratic reform and become material for evaluating Good Corporate Governance (GCG). The research method used is descriptive qualitative with data collection techniques namely observation, interviews and documentation. Informants of this study are Officers and Staff of the Directorate of Aviation Navigation. This study uses the concept of McKinsey's 7s theory with indicators namely Strategy, Structure, System, Skill, Leadership Style, Staff and Shared Values. The results of the study show that the dominant indicators are applied by the Directorate of Aviation Navigation, namely System and Structure where the application of online-based public services is dominantly used and also the application of the Standard Operating Procedure (SOP). While the indicator that is not used is Skill, where training for each position must be further improved. The implementation of Good Corporate Governance (GCG) through Bureaucratic Reform can help government agencies realize a government system in accordance with the values ​​contained in Good Corporate Governance (GCG)